IMPLEMENTATlON OF THE ONE-STOP INTEGRATED SERVICE POLICY lN THE LICENSING SECTOR AT THE ONE-ST0P INVESTMENT AND 0NE-STOP SERVlCE OFFICE OF BARITO KUALA DISTRICT (AN ANALYSIS STUDY OF THE IMPLEMENTATION OF BUILDING APPROVAL (PBG)) - Rahmadian, Muhammad Rif’han; Asmu’I; Syafari, Muhammad Riduansyah (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The Public Service Law and PresidentiaI Regulation No. 97/2014 on the Implementation of 0ne-Stop Integrated Services mandate the central and local governments to implement this policy. This research aims to analyze the impIementation of the one stop service policy in Barito Kuala Regency. In addition to building an ideal model of one-stop service policy implementation, this research uses qualitative research based on the identification of premises and problems. The purpose of this exploration is to describe and dissect 1) the perpetration of the One- Stop Integrated Service Policy at the Investment and One- Stop Integrated Service Office of Barito Kuala Regency; 2) Aspects that support and hamper the perpetration of the one- stop service policy in Barito Kuala Regency. This disquisition uses a qualitative path with a case study of the phenomenon with the disquisition motive being DPMPTSP in Barito Kuala Regency. Data processing techniques used are interviews with informants in accordance with the formulation of the problem, document analysis and field observations in agreement with the exploration object’s, data analysis techniques are processed in data collection by reducing data. The results showed that the Barito Kuala Regency Government had implemented the PTSP policy, but in its implementation, the delegation of license authority occurred GAP between DPMPTSP and technical SKPD, out of 158 permits, only 54 permits were delegated to PTSP. Supporting and inhibiting aspects in policy implementation: 1) the tendency of local government and implementor attitudes, 2) PTSP coordination communication with technical SKPD occurs egosectoral 3) inadequate resources that understand limited information techniques (IT), 4) bureaucratic structure, Standard Operating Procedures (SOP) and Service Standards (SP) to match service promises. The suggested policy implementation models are, 1) improving the transmission of delegation of authority policies to be clear, 2) improving HR competencies with education and training, 3) frahmentation of support for local government attitudes regarding leadership commitment, 4) increasing government support committed to delegation of authority. From the results of the discussion that the DPMPTSP Implementor with the tennis SKPD related to licensing services procedurally coordination between SKPDs experienced obstacles where there was a GAP, because each SKPD had its own application of rules with different interpretations.